(untitled) - Medical University of Ohio Foundation (United States, 2007)
Features an interactive cadaver dissection. This tutorial uses cadaver photos combined with a layering technique that allows the student to peel away layers of the human body to reveal structures beneath the surface. It also offers animations, radiologic imaging, audio pronunciations, and a comprehensive quizzing tool.
Keywords: Giải phẫu học,Giải phẫu người,Anatomy,Human anatomy